Cognitive characteristics and functional physical domain in elderly assessed in a city inside of Amazonas: study transverse - Oliveira, Higor Gregore Alencar (2020)
This article explains a cross-sectional study with 50 elderly people. The work focused on a group of elderly people, in their homes, in a city in the interior of Amazonas, regarding cognitive and physical-functional aspects. The group is characterized by the majority being female, with less than five years of schooling, with severe cognitive impairment and with an alarming decline in physical-functional function.